Diel Feeding Rhythm and Grazing Selectivity of Small-Sized Copepods in a Subtropical Embayment, the Northern South China Sea - He, Xuejia; Wang, Ziyu; Bai, Ziqing; Han, Liuyu; Chen, Mianrun (Frontiers in Marine Science, 2021)
Small marine copepods are key components of the pelagic food webs in Chinese coastal waters, but very few studies have addressed their trophodynamics, with even fewer studies addressing their diel feeding rhythms. In this study, the diel feeding rhythm and grazing selectivity of the copepod assemblage in Daya Bay during Sept. 30-Oct. 2, 2014, were studied based on gut pigment analysis. Small copepods (body length <1.5 mm) including Paracalanus parvus, Temora turbinata, Acrocalanus gibber, Temora stylifera, Euterpe acutifrons, and Acrocalanus gracilis, accounted for 73.9-100% of the total copepod abundance. The copepod assemblage generally exhibited a diurnal feeding pattern, characterized by a higher gut pigment content and ingestion rate during the daytime, consistent with variation in the ambient Chl a concentration. Fifty-five percent of the phytoplankton standing stock per day was consumed by the copepod assemblage, wherein diatoms, prymnesiophytes, and cyanobacteria were the main prey items with average contributions of 19.4 to 32.9 % to the gut pigment contents. The copepod assemblage showed a strong feeding preference for prymnesiophytes, a weak feeding preference for diatoms, and avoidance of cyanobacteria. These results suggest a strong top-down control on phytoplankton community, especially on small groups from small copepods in the Daya Bay ecosystem.